IMPROVEMENT OF INCOME AND COST ACCOUNTING IN THE ACTIVITY OF ENTERPRISES (Marketing Journal, 2025)
The "revenue – cost – profit" analysis system in financial management serves as a critical tool not only for small and medium -sized enterprises but also for large corporations in making strategic and operational management decisions . This system involves an in -depth analysis of cost structures, production processes, pricing strategies, and various factors influencing financial performance . 112 Such an approach enables enterprises to optimize expenditures, ensure efficient resource allocation, and enhance profitability . Based on the research findings, conceptual approaches and practical recommendations for improving financial management efficiency have been developed , aiming to enhance economic stability and competitiveness in the corporate sector .
Keywords: revenue; costs; profit; enterprise; valuation; market; strategy; reporting; client; analysis